Defining the Dimensions of National Security, Financial Security and Food Supply Chain in Ukraine - Iryna Markina; Yuriy Safonov; Oksana Zhylinska; Dmytro Diachkov; Elena Varaksina (International Journal of Supply Chain Management, 2018)
The article justifies the relevance and necessity of defining and analyzing national security and its components. It considers the main conceptual approaches to defining the notion of national security. This is an original vision on what the term national security stands for. The following main components of the national security are characterized: national military, economic security (including financial and food supply chain security), cybersecurity as an integral part of the informational security, societal stability. The components of the national security are analyzed through the system of global indexes: Global Peace Index, Per capita nominal GDP, Index of Economic Freedom, Global Food Security Index, Global Cybersecurity Index, and Social Progress Index. The strategic directions of the development of the Ukrainian national security are defined according to individual components.